Geologia, petrografia e geoquímica de dois plútons graníticos isotrópicos da região de Canaã dos Carajás (PA) e suas afinidades com as suítes graníticas da Província Carajás - AFONSO, Jully Mylli Lopes (2018)
The isotropic granitic plutons that outcrop in the central-western portion of the Canaã dos Carajás area are intrusive in Archean granitoids and until this work had not been described in the literature. They are formed by hololeucocratic monzogranitic rocks, which has hypidiomorphic and equigranular texture. They presents evolved granites aspect, where biotite is the single ferromagnesian mineral and is often associated with fluorite, and also allanite, zircon, apatite and epidote. The changes in subsolidus stage are defined by the occurrence of albite, sericite, epidote and chlorite. The frequent presence of granophyric intergrowth and fluorite points out to a shallow crustal level emplacement of these bodies within significant fluids activity during the final crystallization stage. They show both geochemical behavior and textural pattern that distinguish them of Archean granitic associations of Carajás, but leave clear its affinities with intraplate granites A-type, with a crustal origin (A2 subtype) and those of reduced character (Intrusion II) to weakly oxidized (Intrusion I), both featuring high FeOt/(FeOt + MgO) - ≥ 0.91 ratios. The amplitude of the negative Eu anomaly shown by these rocks as well as low La/Yb ratio is an evolved granites characteristic that differ from those of oxidized character constituting the Jamon Suite, but approaching them to the reduced granites, particularly those of Serra dos Carajás Suite. The occurrence of magnetite justify the low to moderate SM values, and enforcing the reduced to weakly oxidized character of these rocks, and its analogies with the Serra dos Carajás suite. The existing geochemical contrasts between the studied plutons and the granite of this suite, which on average, is noted a greater FeOt, MgO, CaO, TiO2, Sr, Ba, Nb and Zr enrichment on the firsts, may suggest that the source of its magma and/or magmatic evolution processes were not fully coincide with those already identified for the Paleoproterozoic suites. However, despite significant advances in the knowledge of these granitic bodies, there is still needed to deepen the study of the magmatism nature, especially from obtaining mineral chemistry data, precise geochronological (U-Pb) and isotopic (Lu-Hf) data. Such goals should compose the main objectives of the work plan for the development of the author's dissertation at the Graduate Program in Geology and Geochemistry - UFPA.